Cobrança e renegociação de tributos em atraso no Brasil: análise da estrutura de incentivos do programa de transação tributária da Lei nº 13.988, de 2020 - Morais, Cristiano (2021)
Governments use various instruments to set their tax collection policies, which includes, among them, granting amnesties. Poorly designed programs can bring negative effects to tax collection and tax compliance. In Brazil, over the last 20 years, a type of amnesty program known as “Refis” has become frequent, with unsatisfactory results. With the stated purpose of changing this situation, in 2019, Provisional Measure nº 899 was issued, and converted into Law nº 13,988, of 2020, which instituted a new program for pardoning tax debts, using the offer in compromise institute. This study aims to analyze whether this new federal program has the potential, according with economic theory, to increase tax collection and improve future compliance, focusing on the incentives generated for taxpayers by the established procedures. The results indicate that the design of the new public policy has theoretical aptitude to improve tax collection and compliance, generating the correct incentives to the agents. With game theory, it was evidenced that the tax compromise, by enabling agreements with reciprocal concessions, allows the tax authorities and taxpayers with low payment capacity to reach a new balance in the tax collection relationship, with an increase in economic efficiency. The use of the Principal-Agent model demonstrated that the adverse selection and moral hazard problems were addressed by the new debt compromise program, given the screening, monitoring and auditing mechanisms established by the program’s rules. In addition, the importance of using behavioral approaches to improve the effectiveness of tax compliance policies was identified. The main limitation of the research refers to the simplification carried out in the theoretical models and the limited data available due to the novelty of the program. The results achieved can be used as a reference for further studies and comprehensive evaluations of the tax-debt comprimise program, in particular for the assessment of its impact, through field experiments, as well as can contribute to subsidize the debates and decisions of the political class related to the recurring claims for establishing new “Refis” amnesties